O desenvolvimento da competência para o trabalho em equipe a distância com o uso do metaverso Second Life - Gomes, Ana Cláudia Bilhão (Universidade do Vale do Rio dos Sinos, 2012)
This study intends to identify whether and how the use of metaverse technology might contribute to the development of the teamwork competence in distance education courses. The research context was an Undergraduate Technology Course in Human Resources Management at the University of Vale do Rio dos Sinos in a distance learning activity. The method used was the “Design Research”, a process of using knowledge for modeling and creating artifacts for application and generation of theoretical and practical knowledge. The device developed is a training methodology for the development of individual teamwork competence in distance education using the metaverse technology. The methodology consists of: a) diagnostic instruments; b) modeled environment in the Second Life metaverse; c) training for use of the metaverse; d) workshops; and e) the realization of an event and final evaluation. The purpose was the development of individual teamwork competence by a challenge activity proposed to six voluntarily students, considering: a) the training in the use of technology; b) attending virtual meetings work; and c) the creation of the 1st Meeting of Human Resources Professionals and Students in Second Life. The evaluation of the method indicated that the main contribution to the development of teamwork skills in the metaverse occurs through their educational affordances, once the metaverse was perceived as an area of experience which the activities can be performed in, which students will experience various situations and will have to set goals and make their choices, take decisions and take action to put them into practice. Thus, knowledge may become skills and attitudes to face different problem situations related to teamwork. The lessons learned are related both to the development of the competence investigated with regard to the use of technology. In summary, the participants found the following possibilities for technology metaverse contribute to the development of individual teamwork competence: a) building of a context for the development of teamwork competence; b) simulation of situations that give people plan, act and interact; c) application of management techniques and practical activities; d) development of interpersonal relationships; e) complement of presently activities, especially those related to education; and f) promotion of group activities even at a distance. In relation to the device developed the main areas for improvement identified were: a) inadequate time of the meetings; and b) short time of interaction. Regarding technology used, there are also points to be considered: a) difficulties associated technology resources used by participants (connection Internet and hardware) and instability of the Second Life platform (software).
Keywords: Competências; Metaverso; Second life; Educação a distância; Gestão de Recursos Humanos; Trabalho em equipe; Competences; Teamwork; Metaverse; Distance education; Human resource management; ACCNPQ::Ciências Sociais Aplicadas::Administração